Characterization of Antigenic MHC-Class-I-Restricted T Cell Epitopes in the Glycoprotein of Ebolavirus - Jonathan Powlson; Daniel Wright; Antra Zeltina; Mark Giza; Morten Nielsen; Tommy Rampling; Navin Venkatrakaman; Thomas A. Bowden; Adrian V.S. Hill; Katie J. Ewer (Cell Reports, 2019)
Summary: Ebolavirus causes highly lethal hemorrhagic fever in humans. The envelope-displayed viral glycoprotein (GP) is the primary target of humoral immunity induced by natural exposure and vaccination. No T cell epitopes in the GP have been characterized in humans. A phase I clinical trial of a heterologous prime-boost vaccination regime with viral vectors encoding filovirus antigens elicits humoral and T cell responses in vaccinees. The most frequently recognized peptide pools are deconvoluted to identify the minimal epitopes recognized by antigen-specific T cells. We characterize nine immunogenic epitopes on the Ebolavirus GP. Histocompatibility leukocyte antigen (HLA) typing with in silico epitope analysis determines the likely MHC class I restriction elements. Thirteen HLA-A and -B alleles are predicted to present the identified CD8+ T cell epitopes, suggesting promiscuous recognition and a broad immune response. Delivery of the Ebolavirus GP antigen by using a heterologous prime-boost approach is immunogenic in genetically diverse human populations, with responses against multiple epitopes. : Vaccination can induce both T cell and antibody responses to Ebola virus glycoprotein. Powlson et al. describe CD8+ T cell epitopes and recognition of these epitopes through multiple HLA alleles. Detailed characterization of immunity contributes to our understanding of the potential application of vaccines in diverse populations. Keywords: Ebola, CD8 T cells, vaccine, humans, epitope-mapping, HLA-restriction